The Power of Now : A Guide to Spiritual Enlightenment - Tolle, Eckhart (London Hodder and Stoughton Ltd., 2005)
To make the journey into The Power of Now we will need to leave our analytical mind and its false created self, the ego, behind. From the beginning of the first chapter we move rapidly into a significantly higher altitude where one breathes a lighter air, the air of the spiritual. Although the journey is challenging, Eckhart Tolle offers simple language and a question and answer format to guide us. The words themselves are the signposts.
Include Notes.
Keywords: Spiritual Life -- Spirituality